The Impact of peptide flanking residues on predicting peptide-MHC-II binding interactions using convolutional Neural Networks - Daumas, Tshenolo Thato Eustacia (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.